2017
DOI: 10.1002/celc.201700410
|View full text |Cite
|
Sign up to set email alerts
|

A Fe/Mn‐Based Prussian Blue Analogue as a K‐Rich Cathode Material for Potassium‐Ion Batteries

Abstract: The reversible intercalation of K+ into graphite has spurred interest in new rechargeable battery chemistries based on potassium ions. The viability of commercializing potassium‐ion batteries (KIBs) is critically dependent on the availability of pre‐potassiated cathode materials, and the compatibility between the electrolyte and electrode components; which have yet to be fully explored. Herein, we report a Fe and Mn based K‐rich Prussian Blue analogue, which can be used as the cathode of rechargeable KIBs to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 61 publications
1
68
0
Order By: Relevance
“…g) F1 XPS patterns of a bare Prussian‐white (K 1.6 Mn[Fe(CN) 6 ] 0.96 ·0.27H 2 O) electrode, before and after 10 cycles in EC:DEC and PC:FEC electrolytes. Reproduced with permission . Copyright 2017, Wiley‐VCH Verlag GmbH & Co. KGaA.…”
Section: Potassium‐ion Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…g) F1 XPS patterns of a bare Prussian‐white (K 1.6 Mn[Fe(CN) 6 ] 0.96 ·0.27H 2 O) electrode, before and after 10 cycles in EC:DEC and PC:FEC electrolytes. Reproduced with permission . Copyright 2017, Wiley‐VCH Verlag GmbH & Co. KGaA.…”
Section: Potassium‐ion Batteriesmentioning
confidence: 99%
“…An operando XRD study identified reversible structural changes that engender this material with an excellent electrochemical performance that is attributed to its open and flexible framework. Jiang et al showed that FEC additives are preferred when PW K 1.6 Mn[Fe(CN) 6 ] 0.96 ·0.27H 2 O in an EC:DEC electrolyte was used because K + ‐conducting passive layers are formed on the K metal. However, caution is required because FEC reduction results in the release of HF, which may degrade the PW materials following exposure to an acidic electrolyte (Figure g).…”
Section: Potassium‐ion Batteriesmentioning
confidence: 99%
“…Copyright 2017, American Chemical Society; e) illustration of potassium deposition in different electrolytes. Reproduced with permission . Copyright 2017 John Wiley and Sons.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Besides, XRD analysis indicates that the open and flexible framework renders the structural stability during the K + extraction/insertion process. On the other hand, the PB analogue of K 1.6 Mn[Fe(CN) 6 ] 0.96 ·0.27H 2 O was then developed . It delivers a discharge capacity of 115 mAh g −1 with two voltage plateaus of 3.9 V and 4.1V, respectively, which means that the significant impact of electrolyte on the performance of PIBs.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…By contrast, the research of PIB is still in the initial stage. [7][8][9][10][11] As an emerging substitute, PIB exhibits impressive characteristics and extensive commercial prospects. On the one hand, it has been confirmed that the long cyclic performance thermodynamic of graphite anode in PIB is more stable than in SIB, which largely broadens the possibilities of carbon derivatives for PIB.…”
Section: Introductionmentioning
confidence: 99%